Influence Promotıon, Perceıved Of Rısk And Trust Towards Onlıne Shoppıng Usıng Technology Acceptance Model - Ilham Fitriadi; Ahmad Rifani; Maya Sari Dewi; Rusdayanti Asma; Irwansyah, Irwansyah (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The purpose of this study is to explore the conceptual model for the attitude and perception investigate customer interest in doing online shopping influenced by promotion, risk perception and trust. Samples collected were 117 respondents which found online and directly to respondent. The use of an online questionnaire among others, to ensure that respondents fill is correct respondents who are used to access the internet. The next filter to ensure respondents had online shopping, at the beginning of the questionnaire has been given the question of whether the respondent ever online shopping. There is no limit to the number of respondents in online shopping, which goods are purchased and through the website / online shopping portal specific. Technology Acceptance Model (TAM) is a popular model that was adopted because it is a model that was developed to measure the level of acceptance of the technology, according to the model in this study. The analysis technique used in this research is Structural Equation Model (SEM) with AMOS. The results showed that the promotion and trust influence the perceived usefulness and perceived ease of use in online shopping, except for the variable trust has no effect on the perceived usefulness. And both perceptions significantly influence the attitudes and interest in online shopping. But the perceived of risk was not significant effect on trust and perceived ease of use.